Hydrodistillation, Solvent Free Microwave Assisted Extraction and Headspace-Solid Phase Microextraction for Analysis of Essential Oil of Flowers of Helichrysum aucheri - Abroomand Azar, Parviz; Torabbeigi, Marzieh; Saber Tehrani, Mohammad; Waqif Husain, Seyed (Asian Journal of Chemistry, 2010)
In this study, the essential oil of flowers of Helichrysum aucheri is investigated. The essential oil of flowers of Helichrysum aucheri collected from Abasabad Valley of Hamedan, in June 2008, were isolated by solvent free microwave assisted extraction (SFME) and headspace-solid phase microextraction (HD-SPME) with polydimethylsiloxane/divinylbenzene fiber as solid phase and comparison the compositions of the essential oils extracted by these methods with hydrodistillation method. The volatile compounds which obtained by hydrodistillation, solvent free microwave assisted extraction and headspace-solid phase microextraction were analyzed by means of GC/MS. α-Pinene (38.5 %), β-caryophyllene (23.0 %), 1,8 cineole (12.0 %), were the major components in hydrodistillation method. Isoborneol (28.2%), β-caryophyllene (12.9 %), δ-cadinene (6.3 %), bornyl acetate (6.0 %) were found to be the main constituents in the solvent free microwave assisted extraction method. The main compounds which entered by headspace-solid phase microextraction were carvacrol (37.7 %), α-pinene (19.7 %) and β- caryophyllene (8.5 %).